Interior design elements and facilities for disabled people in the mosque: are we facilitating the "needs"? - Jasmani, Ismail (2013)

(untitled)
Mosque is the place of people or ‘jammah’ to pray in worship of ALLAH serves more than as congregational prayer places five times daily .The mosque is as a community centre, learning centre, the seat of government, Welfare centre, Prison, Hospital and legitimate recreational activities which is stated in the holy Quran and hadiths. Means that all Muslim generations, races whether normal and handicapped community to enjoy the facilities at the mosque for the seek of one ummah.